Mediasi Penal sebagai Penyelesaian Pidana Ringan Pondok Pesantren Putra Al-Ishlah Malang; Perspektif Maqashid Syariah Ibnu Ashyur - Rofrofil Akmal, Ahmad Wildan; Nur Syifa, Siti; Saifullah, Saifullah (IAIN Langsa, 2025)
This article aims to examine the implementation of penal mediation as a form of resolving minor criminal offenses committed by students at Al-Ishlah Putra Islamic Boarding School in Singosari, Malang, and to analyze its application from the perspective of maqashid sharia according to Ibnu Ashur. This article falls under qualitative library research with an empirical legal study approach. The findings show that penal mediation in this pesantren represents a legal resolution that emphasizes educational and restorative values, through mechanisms such as deliberation between the offender, the victim, and the student’s guardian, as well as religious and social sanctions aimed at fostering moral awareness. From the perspective of Ibnu Ashur’s maqashid sharia, this practice reflects efforts to protect the five essential aspects of life—religion, life, intellect, lineage, and property—while also demonstrating a legal approach that is rational, proportional, and oriented toward the public good (maslahah ‘ammah).